An update of the population status and conversation of the leatherback turtle of Terengganu. - Salleh, Brahim; Chan, E. H.; Kassim, Abdul Rahman (1987)
This paper provides information on the nesting population status of the leatherback turtle of Terengganu and reviews the trends observed over the last 35 years. The current annual nesting population is estimated at only 100 female turtles, compared to 613 in the late 1970's, 1424 in the late 1960's and 1779 in the 1950's. It is not known if the current population size can be restored to its former abundance or even maintain itself at its present level. State authorities are intensifying conservation efforts by increasing budget allocation, approving the establishment of a turtle sanctuary, and reviewing and formulating legislation for the protection of sea turtles. Hatchery operation remains a key factor in turtle conservation. Research is conducted to identify ways to improve hatch rates of eggs and to optimise hatchery production. The effects of fishing are highlighted and ways to mitigate their deleterious effects discussed. Efforts are also undertaken to create public awareness on the plight of the leatherbacks.